Him, her, them, or none: misgendering and degendering of transgender individuals. Issue 4 (2nd October 2022) - Howansky, Kristina; Wittlin, Natalie; Bonagura, Darla; Cole, Shana
ABSTRACT: Across three studies people miscategorised transgender individuals through degendering (abstention of pronouns) and misgendering (using gender inconsistent pronouns). Participants described and evaluated an individual who either disclosed a transgender identity or did not in an interpersonal context. In Study 1 ( N = 203), men were more likely to misgender a woman who identified as transgender (vs. did not) and were less likely to explicitly categorise her as a woman. In Studies 2 ( N = 600) and 3 ( N = 593), participants were more likely to misgender and degender transgender women and men (vs. controls). In Study 3, participants who learned a person's pronoun were less likely to degender transgender women. However, providing pronouns did not result in significantly less misgendering overall, nor did it mitigate the degendering of transgender men. Misgendering was a stronger predictor of social connectedness and social categorisation (Study 1) than explicit gender inconsistent categorisations. Misgendering is an insidious indirect form of miscategorisation, more strongly predicting negative social consequences than direct explicit categorisation. While listing one's pronouns mitigates some pronoun disparities, it is not a cure-all for degendering and misgendering.